Orientalism and Colonial Legacies in Bollywood’s Film Earth (1999) - Hamza Hassan; Teo Miaw Lee (Al-Qanṭara, 2023)
Bollywood is considered to be one of the significant cinemas in the world. As the Indian Sub-continent remained a British colony, its society is filled with colonial characteristics, not only in terms of society but also in terms of cinema, culture, linguistics, and literature. The partition of the Indian Sub-continent is considered one of the most important themes in twentieth-century cinema. Earth is a romantic drama-film about the partition of the Indian Sub-continent. This film depicts the period of 1947, focusing on the lives of the individuals who lived during that time. This study examines not just British occupiers’ oriental representation to the colonized locals but also colonial cultural legacies in Indian Sub-continent society as depicted in the film. Edward Said’s postcolonial theory, which includes the key notion of orientalism, has been applied to the film in order to analyze it. Keywords: Orientalism, Colonial Legacies, Post Colonialism, Bollywood, Film Studies, Cinematography